2021
DOI: 10.1038/s41467-021-26836-1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal mixed layer depth shapes phytoplankton physiology, viral production, and accumulation in the North Atlantic

Abstract: Seasonal shifts in phytoplankton accumulation and loss largely follow changes in mixed layer depth, but the impact of mixed layer depth on cell physiology remains unexplored. Here, we investigate the physiological state of phytoplankton populations associated with distinct bloom phases and mixing regimes in the North Atlantic. Stratification and deep mixing alter community physiology and viral production, effectively shaping accumulation rates. Communities in relatively deep, early-spring mixed layers are char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 82 publications
2
47
0
Order By: Relevance
“…In addition, considering the continuous variation in the marine environment, this study also identifies a broad transition zone. The primary cause of this longitudinal environmental gradient in Pacific Ocean is biological oceanographic and biogeochemical mechanisms controlled by physical oceanographic differences, such as seasonal variation of mixed layer depth and transport of water masses (Amos et al, 2019;Diaz et al, 2021), but this environmental gradient is further reinforced by subtle biological processes, such as basin-scale distribution of nitrogen-fixing organisms (Cheung et al, 2020).…”
Section: Longitudinal Environmental Gradientmentioning
confidence: 99%
“…In addition, considering the continuous variation in the marine environment, this study also identifies a broad transition zone. The primary cause of this longitudinal environmental gradient in Pacific Ocean is biological oceanographic and biogeochemical mechanisms controlled by physical oceanographic differences, such as seasonal variation of mixed layer depth and transport of water masses (Amos et al, 2019;Diaz et al, 2021), but this environmental gradient is further reinforced by subtle biological processes, such as basin-scale distribution of nitrogen-fixing organisms (Cheung et al, 2020).…”
Section: Longitudinal Environmental Gradientmentioning
confidence: 99%
“…At the base of the mixed layer, water column stability also affects the flux of nutrients to the surface layer (Carvalho et al, 2017). Previous studies have shown vertical mixing and phytoplankton biomass are consistent with the critical depth at which photosynthesis occurs (Behrenfeld, 2014;Diaz et al, 2021). Vertical mixing also affects grazing by diluting micro-grazers along with phytoplankton (Marra & Barber, 2005).…”
mentioning
confidence: 92%
“…Highly phytoplankton biomass in the subsurface layer in the CIO is the result of a continuous nutrient input into the euphotic zone due to the thermocline shoaling generated by wind‐driven upwelling (Jyothibabu et al., 2015; Thushara et al., 2019). In addition, wind‐driven turbulent mixing process forms an upper‐density layer known as the surface mixed layer, which plays a vital role in explaining the physical processes driving phytoplankton blooms in the upper ocean (Behrenfeld, 2014; Diaz et al., 2021). Mixed‐layer depth (MLD) is thus a central metric commonly studied for understanding phytoplankton variability (Anju et al., 2020; Carvalho et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations